Water harvesting methods and storage structures in Sikkim - Patle, G T (Indian Farming, 2015)
The hilly state of Sikkim has tremendous scope for improving crop productivity through rainwater harvesting. These water harvesting methods and storage structures are helpful to solve the domestic water needs at the time of water scarcity. Harvested rainfall can also aid in providing supplemental irrigation to the field crops. Judicious use and management of harvested rainfall is also possible through adoption and promotion of modern irrigation methods like drip and sprinkler irrigation.